LpCat1 Promotes Malignant Transformation of Hepatocellular Carcinoma Cells by Directly Suppressing STAT1 - Ji, Weidan; Peng, Zhangxiao; Sun, Bin; Chen, Lei; Zhang, Qin; Guo, Minggao; Su, Changqing (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a malignant cancer with rapid proliferation and high metastasis ability. To explore the crucial genes that maintain the aggressive behaviors of cancer cells is very important for clinical gene therapy of HCC. LpCat1 was reported to be highly expressed and exert pro-tumorigenic effect in a variety of cancers, including HCC. However, its detailed molecular mechanism remained unclear. In this study, we confirmed that LpCat1 was up-regulated in HCC tissues and cancer cell lines. The overexpressed LpCat1 promoted the proliferation, migration and invasion of HCC cells, and accelerated cell cycle progression, while knocking down LpCat1 significantly inhibited cell proliferation, migration and invasion in vitro and in vivo, and arrested HCC cells at G0/G1 phase. Moreover, we proved for the first time that LpCat1 directly interacted with STAT1 which was generally recognized as a tumor suppressor in HCC. High levels of LpCat1 in HCC could inhibit STAT1 expression, up-regulate CyclinD1, CyclinE, CDK4 and MMP-9, and decrease p27kip1 to promote cancer progression. Conversely, down-regulation of LpCat1 would cause the opposite changes to repress the viability and motility of HCC cells. Consequently, we concluded that LpCat1 was a contributor to progression and metastasis of HCC by interacting with STAT1.